2020
DOI: 10.1021/jacs.0c08035
|View full text |Cite
|
Sign up to set email alerts
|

P(III)/P(V)-Catalyzed Methylamination of Arylboronic Acids and Esters: Reductive C–N Coupling with Nitromethane as a Methylamine Surrogate

Abstract: The direct reductive N-arylation of nitromethane by organophosphorus-catalyzed reductive C-N coupling with arylboronic acid derivatives is reported. This method operates by the action of a small ring organophosphorus-based catalyst (1,2,2,3,4,4-hexamethylphosphetane P-oxide) together with a mild terminal reductant hydrosilane to drive the selective installation of the methylamino group to (hetero)aromatic boronic acids and esters. This method also provides for a unified synthetic approach to isotopically-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 88 publications
2
24
0
Order By: Relevance
“…Nitroalkane such as nitromethane or nitropropane has been adopted as substrate to couple with phenylboronic acid in the catalytic conditions, but no desired product was observed, judging from 1 H NMR and TLC analysis. The results are consistent with previously reported that the nitroalkane is inherently less reactive than Ar−NO 2 , due to a larger local frontier orbital energy gap (ΔΔ E =1.0 eV) [40] …”
Section: Resultssupporting
confidence: 93%
“…Nitroalkane such as nitromethane or nitropropane has been adopted as substrate to couple with phenylboronic acid in the catalytic conditions, but no desired product was observed, judging from 1 H NMR and TLC analysis. The results are consistent with previously reported that the nitroalkane is inherently less reactive than Ar−NO 2 , due to a larger local frontier orbital energy gap (ΔΔ E =1.0 eV) [40] …”
Section: Resultssupporting
confidence: 93%
“…In addition, reductive amination of amines using CO 2 also constitutes a green methodology to produce N ‐methyl amines [6] . Apart from these approaches, reagents such as (para)formaldehyde, [7] formic acid, [8] dimethyl carbonate, [8f,9] DMSO, [10] Me‐NO 2 , [11] dimethylamines, [12] Me 3 N‐BH 3 [13] and methoxy unit of lignin [14] have been successfully employed to achieve useful N ‐methylamines or N , N ‐dimethylanilines. Traditionally, industrial N ‐methylation reactions are mainly performed using toxic reagents like methyl halides, dimethyl sulfate, dimethyl phosphite and diazomethane [15] .…”
Section: Introductionmentioning
confidence: 99%
“…However, not only the metals but also the metalloids and nonmetals are enjoying increased interest. Notably, phosphorus compounds were recently shown to catalyze C-N coupling reactions [113] and undergo both oxidative additions and reductive eliminations in stoichiometric experiments demonstrating potential as catalysts [114]. Main challenges include the design of the coordination sphere of the main-group element to stabilize active catalysts.…”
Section: Box 1 An Overview Of Homogeneous Catalysismentioning
confidence: 99%